Memorable Tourism Experience: Building Satisfaction and Loyalty of Tourists (Case Study of Medan City, Indonesia) - Elfitra Desy Surya Surya; Bambang Suwarno (Yayasan Riset dan Pengembangan Intelektual, 2023)
This study examines the effect of memorable tourism experience on tourist loyalty mediated by tourist satisfaction in visiting the city of Medan. The research design was built using a causal-descriptive approach and supported by the PLS-SEM 2.8 quantitative method implemented to validate the hypothesis empirically. Survey questionnaires were used to collect data. The sample consisted of 210 tourists who visited the city of Medan, both local and national tourists. The results of the R-square test show a robust model, as seen from the percentage value of the tourist loyalty variable of 0.796, influenced by memorable tourism experience and mediated by tourists of 0.463. Besides that. From the research results, all variables, namely memorable tourism experience, traveler satisfaction, and traveler loyalty, have a significant effect. Traveler satisfaction as a mediating variable has a statistically substantial mediating role, from memorable tourism experiences to building tourist loyalty to tourist destinations in Medan City. These findings will be helpful for the local government and tourism industry players in the city of Medan in developing their goals and increasing tourist visits to the city of Medan and other stakeholders.